Pemenuhan Hak Atas Lingkungan Hidup yang Baik dan Sehat Melalui Konservasi Hutan Adat Wonosadi Berbasis Kearifan Lokal - Hidayatulloh, Muhammad Muslim; Triyanto; Mohd Hairy Ibrahim (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2025)
This study examines how local wisdom-based conservation in the Wonosadi Customary Forest contributes to the fulfilment of the constitutional right to a good and healthy environment in Indonesia. Using a descriptive qualitative approach, data were collected through in-depth interviews, participatory observation, and document analysis conducted between February and June 2025. Fifteen informants were purposively selected, including traditional leaders, members of the forest management group, residents, and village officials. Data were analyzed thematically through coding, categorization, and interpretation, supported by methodological and source triangulation. The findings demonstrate that local values, such as pamali (customary prohibitions), rituals, and customary institutions, form a participatory governance system that effectively regulates forest use and maintains ecological balance. Conservation practices have improved vegetation cover, air quality, and spring water availability while reducing ecological risks such as floods and landslides. These efforts also support community welfare through agroforestry and the sustainable use of non-timber forest products. Overall, the model contributes to Sustainable Development Goals (SDGs) 3, 6, 13, 14, and 15, demonstrating that conservation rooted in local wisdom can serve as an effective and adaptive strategy for sustainable resource management. However, its long-term success depends on strong social institutions, intergenerational knowledge transmission, and cultural cohesion.